Meningococcal infection in children in the period 2012–2021. Main results of a retrospective multicenter study, issues of the day - A. A. Vilnits; Yu. V. Lobzin; N. V. Skripchenko; L. N. Mazankova; O. I. Klimova; A. Yu. Rtishchev; I. M. Osmanov; K. V. Markova; N. H. Tkhakushinova; G. P. Martinova; A. U. Sabitov; R. K. Babik; et al. (Журнал инфектологии)
The heavy burden of meningococcal infection is associated not only with life-threatening complications in the acute period and high mortality in invasive forms of the disease, but also with severe consequences in survivors, who are not recorded in our country.The aim of study: to analyze clinical manifestations, complications of the acute period and outcomes of invasive forms of meningococcal disease in children in various regions of the Russian Federation.Materials and methods: an analysis of data from 1327 inpatient medical records of children with an invasive meningococcal infection from 14 regional centers of the Russian Federation for 2012-2021 was carried out (28.3% of cases of the disease in children in the represented federal districts).Results: it was found that young children predominated among the patients – the median was 27.4 (10.7-70.4) months. Complications of the acute period, often combined, were observed in 47.6% of cases. The development of septic shock was noted in 30.4%, Waterhouse-Friderichsen syndrome in 6.6%, carditis in 2.9%, cerebral edema in 15.7%, arthritis in 1.4% of cases; the formation of hydrocephalus, subdural effusion, sensorineural hearing loss in 1.8%, 0.6%, 1% of children, respectively. The presence of soft tissue necrosis requiring surgical intervention was noted in 3.5% of cases. Mortality rate was 10.1%. At the time of discharge from the hospital, 30% of children had complications associated with meningococcal infection: organ dysfunction/ failure in 13.2% of patients (severe in 1.3%), cerebral insufficiency in 19.6%; severe psycho-neurological deficits, sensorineural hearing loss, problems associated with the need for orthopedic/surgical interventions accounted for 0.7%, 0.6% and 0.8%, respectively.Conclusion. Considering the epidemiological features of meningococcal infection – the risk of a sharp increase in morbidity in short periods of time, the life-threatening nature of the disease itself, it is necessary to remain alert to these risks and take all possible measures to prevent the disease using all available means, the most effective of which is vaccine prevention.